Análisis del ambiente escolar en la institución educativa Santa Ana innovación educativa y construcción de paz (Memorias Sifored - Encuentros Educación UAN, 2023)
This paper presents the analysis of results of the first phase of my master's research, in which the school environment in the Santa Ana educational institution was evaluated. To this end, a Likert-type survey was conducted among tenth and eleventh grade students, who have been training in the same place for several years, know the teaching population and have spent a lot of time interacting within this institution. A study conducted by Precisa Medición Estratégica de México in 2018, which sought to assess perception in a wide variety of institutions, was found and adapted. The research questions were adapted to the school context to facilitate understanding and obtain punctual results through qualitative questions classified as relationship between students, norms of coexistence, problem solving and actions. The results showed a high rate of verbal aggression (61%), rumors (60%), threats (53%), teasing (57%), blackmail (47%) and theft or damage to personal objects (46%). In conclusion, it was determined that there are behaviors among students that affect the relational quality and the school environment, as well as the performance of the training, learning and teaching process. These problems can be externalized through physical aggression or cyberbullying.
Keywords: peace building; class environment; class bullying